Can High Interest Rates Stop Regional Currency Falls?: The Asian Experience in 1997-98 - Kenichi Ohno; Kazuko Shirono; Elif Sisli (Asian Development Bank Institute (ADBI), 1999)
During the Asian crisis, some crisis-hit economies raised domestic interest rates persistently in an effort to appreciate their currencies. Although Asian currencies eventually stabilized, it is still debated whether high interest rates contributed to the restoration of stability. Correlation and causality analyses using daily data show that the relationship among interest rates, exchange rates and external financial variables changed significantly when the crisis started. During the height of the crisis, currencies in the region exhibited high synchronization and mutual causation, which had not been visible in the pre-crisis period. Japanese and U.S. financial variables also influenced the movements of the Thai baht and the Korean won. By contrast, domestic interest rates suddenly lost their impact on exchange rates as the crisis worsened. The Asian currency turmoil and subsequent return to stability was a regional phenomenon, in which interest rate policies of individual economies did not seem to have any significant impact on calming collective market psychology.
hdl:11540/4113
Keywords: 330